Relative Sea‐Level Changes During Roman Times in the Northwest Mediterranean: The 1st Century A.D. Fish Tank of Forum Julii, Fréjus, France. Issue 4 (21st May 2013) - Morhange, Christophe; Marriner, Nick; Excoffon, Pierre; Bonnet, Stéphane; Flaux, Clément; Zibrowius, Helmut; Goiran, Jean‐Philippe; Amouri, Mourad El
<x xml:space="preserve">Abstract</x> Fish tanks become fashionable throughout the Mediterranean area between the 1st century B.C. and the 1st century A.D. Because of this narrow chronological window, and their link to former sea level, they constitute precious archives to investigate relative sea level (RSL) since the Roman period, especially when combined with fossilized marine benthos found attached to the fish tank walls. Here, we present new results from an integrated analysis of a fish tank located in the Roman colony of Fréjus, Southeastern France. The well‐preserved biological remains on the fish tank wall allow us to estimate an RSL rise of 40 ± 10 cm at Fréjus since Roman times, consistent with a recently published range of −32 to −58 ± 5 cm for the Northwestern Mediterranean for the same time. By contrast, the findings contradict the ∼150 cm of RSL change since Roman times reported for the Northwestern Mediterranean by some authors. © 2013 Wiley Periodicals, Inc.